Some generalized nonexpansive mappings and weak normal structure - Piątek, Bożena (Topological Methods in Nonlinear Analysis, 2024)
We consider relations between normal structure of a Banach space and the fixed point property for various classes of generalized nonexpansive mappings under additional assumptions, such as that of continuity. In this way we answer some open questions about the behaviour of such maps.